Within-prison drug injection among HIV-infected male prisoners in Indonesia: a highly constrained choice. - Culbert, Gabriel J; Waluyo, Agung; Iriyanti, Mariska; Muchransyah, Azalia P; Kamarulzaman, Adeeba; Altice, Frederick L (Drug and alcohol dependence, 2015)
In Indonesia, incarceration of people who inject drugs (PWID) and access to drugs in prison potentiate within-prison drug injection (WP-DI), a preventable and extremely high-risk behavior that may contribute substantially to HIV transmission in prison and communities to which prisoners are released.
Keywords: Adult; Attitude; Heroin; HIV Infections; Humans; Indonesia; Male; Methadone; Narcotics; Needle Sharing; Opioid-Related Disorders; Prevalence; Prisoners; Prisons; Risk-Taking; Substance Abuse, Intravenous